Updated Perspectives on the Diagnosis and Management of Neonatal Invasive Candidiasis - Daniel K; Greenberg RG; Boutzoukas A; Katakam L (Dove Medical Press, 2023)
Katherine Daniel,1 Rachel G Greenberg,2,3 Angelique Boutzoukas,2,3 Lakshmi Katakam4 1Duke University School of Medicine, Durham, NC, USA; 2Department of Pediatrics, Duke University, Durham, NC, USA; 3Duke Clinical Research Institute, Durham, NC, USA; 4Department of Pediatrics, Neonatal-Perinatal Medicine, Durham, NC, USACorrespondence: Lakshmi Katakam, Department of Pediatrics, Neonatal-Perinatal Medicine, 2400 Pratt Street, North Pavilion Building, 8th Floor, Durham, NC, 27705, USA, Tel +1 919 681 6035, Fax +1 919 681 6085, Email lakshmi.katakam@duke.eduAbstract: Invasive candidiasis can cause severe illness in immunocompromised hosts, such as premature infants. Clinical presentation in neonates is variable and often characterized by non-specific signs with potential to involve several organ systems. Awareness of risk factors for Candida infections in the neonatal intensive care unit (NICU) can aid in screening infants with signs and symptoms of generalized illness. Cultures of blood, urine, and cerebrospinal fluid are the main diagnostic tools available in this population of infants, but several biomarkers and alternate identification methodologies such as 1,3-β-D-glucan, serum mannan or anti-mannan, and T2 magnetic resonance testing are being studied in the neonatal population. Prompt diagnosis of Candida infection, in conjunction with a comprehensive assessment of disease progression and organ involvement, is critical for optimizing treatment and patient outcomes. Supportive care and systemic antifungal medications remain the mainstay of treatment, and the efficacy and safety of newer therapeutic agents continue to be evaluated in neonates. Disease prevention strategies must be thoughtfully implemented and customized to each individual NICU based on local incidence of Candida infection, practice patterns, and risk factors, and may include prophylactic antifungal therapy. This review summarizes the evidence for current approaches to diagnosis and management of neonatal invasive candidiasis and provides an overview of the newer diagnostic tools and therapeutic agents on the horizon.Keywords: Candida, infant, biomarkers, amphotericin B, fluconazole, prophylaxis